2019
DOI: 10.1029/2018jb017073
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Acoustic Multipole Waveform Inversion at Yasur Volcano, Vanuatu

Abstract: Acoustic waveform inversions can provide estimates of volume flow rate and erupted mass, enhancing the ability to estimate volcanic emissions. Previous studies have generally assumed a simple acoustic source (monopole); however, more complex and accurate source reconstructions are possible with a combination of equivalent sources (multipole). We deployed a high‐density acoustic network around Yasur volcano, Vanuatu, including acoustic sensors on a tethered aerostat that was moved every ∼15–60 min. Using this u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
103
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(117 citation statements)
references
References 56 publications
14
103
0
Order By: Relevance
“…These observations suggest that, for the data considered here, a monopole source provides a realistic and sufficiently accurate estimate of VFRs (supporting information Figure S5). This is consistent with previous results from Iezzi et al () at Yasur and Fee et al () at Sakurajima. One important implication of this observation, if confirmed to have more general validity, is that if waveform inversion was implemented for use in real‐time volcano monitoring, a monopole‐only source would provide realistic estimates of atmospheric VFR.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These observations suggest that, for the data considered here, a monopole source provides a realistic and sufficiently accurate estimate of VFRs (supporting information Figure S5). This is consistent with previous results from Iezzi et al () at Yasur and Fee et al () at Sakurajima. One important implication of this observation, if confirmed to have more general validity, is that if waveform inversion was implemented for use in real‐time volcano monitoring, a monopole‐only source would provide realistic estimates of atmospheric VFR.…”
Section: Discussionsupporting
confidence: 94%
“…(c) Detail of the time history of volume flow rate (top panel) and horizontal dipole (middle and bottom panels) for EV1 in (a). Also shown (top panel) a comparison between the volume flow time series with no detrending applied (black dashed line), with simple linear detrending following the methods of Iezzi et al (, yellow dashed line), and after application of FWZPZF detrending following the methods of Johnson and Miller (); (d) Azimuth of the horizontal dipole for EV1 in (a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We model the acoustic radiation as a baffled piston in a half space. In recent years, numerous studies have shown that topographic scattering is important, even for near‐field observations (Fee et al., 2017; Iezzi et al., 2019; Kim & Lees, 2011, 2014). We contend that we can neglect topographic scattering here due to the low frequencies that we consider and because the spectral content is similar across all stations in the network (Figure S1; Cannavò et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As part of concurrent studies [Iezzi et al 2019;Jolly et al 2017;Matoza et al 2017], a temporary infrasound and seismic network was set up around the cone. Two stations from this network (YIB22 and YS01), lo-cated~700 m from the vent area, are used in this pa-Volcanica 3(2): 183 -204. doi: 1 .3 9 9/vol.…”
Section: Methodsmentioning
confidence: 99%